Nickel-Iron-Zinc Phosphide with Three-Dimensional Petal-Like Nanostructure as a Highly Efficient Electrocatalyst for Oxygen Evolution Reaction in Alkaline Electrolytes. (1st August 2022) - Parkash, Anand; Solangi, Nizamuddin; Seehar, Tahir Hussain; Ali, Salamat; Larik, Rimsha; Bajaber, Majed A.; Shahid, Hira; Jatoi, Abdul Sattar
Abstract : A 3D petal-like Transition metal phosphide (TMP) doped with Zn 2+ on nickel foam was developed by a low-temperature phosphating approach for effective oxygen evolution reaction (OER), premised on the idea of developing TMP for high-efficiency water splitting. The loading of Zn 2+ on the P surface raises the electron density, which is favorable for capturing protons in the water during the reaction, accelerating the electron transport rate, and accelerating the OER process. At the same time, we evaluated the optimal Zn 2+ content ratio. When the Zn 2+ to Fe 3+ molar ratio is 0.5, the NiFeZnP-0.5/NF exhibits the best OER performance. The catalyst displays an overpotential of ∼136 mV at 10 mA cm −2, ∼201 mV at 100 mA cm −2, Tafel slope of 35 mV dec −1 in 1 M KOH solution, and remains stable over 6 h. The Cdl of the NiFeZnP-0.5/NF electrode is 4.3 mF cm −2, which increased by 5 times than the NiFeZn-LDHs/NF. Electrocatalysts' high performance is due to their superior electrical conductivity and synergy with the substrate. Our research provides a realistic solution in the field of electrocatalysis.